Stil in der neutestamentlichen Exegese: Definition, Methodik und Konkretisierung am Beispiel des Lukasevangeliums - Kowalski, Beate (Protokolle zur Bibel, 2003)
"The study of style and stylistics in New Testament research is to a great extent static and inadequate, and . . . the scope of these studies is very limited" (J.E. Botha). Only a very few scholars have dedicated their research to this question. The following article gives an outline ofthis problem within a short Forschungsbericht. The studies can be systematized in three differerent categories of style: author-, text-, and recipient-oriented definitions of style. The development of an adequate definition of style has to comprise these three levels of communication. Based on this the second part of the article deals with a description of a stylistic-critically method. The gospel of Luke serves as an example to clearly define the definition.